2019
DOI: 10.4314/jasem.v23i6.7
|View full text |Cite
|
Sign up to set email alerts
|

Beta-sitosterol with antimicrobial property from the stem bark of pomegranate (<i>Punica granatum</i> Linn)

Abstract: The aim of this research was to isolate and characterize bioactive substances that may be responsible for the ethno medicinal uses of Punica granatum. Phytochemical constituents and characterization led to the isolation of Beta-Sitosterol from the hexane extract of the stem bark of the plant. The structure of the isolated compound was elucidated by spectra data including FTIR, 1D-and 2D-NMR. The compound was active against Salmonella typhi and Escherichia coli with zones of inhibition of 20 and 35 mm respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Column chromatography and crystallization of fraction 1 (Fr. 1) yielded white needle-like crystals (19 mg) which were separated from the mother liquor and were named compound 1 and identified as β-sitosterol by comparing with previous literature reports . Fraction pool Fr.…”
Section: Resultsmentioning
confidence: 83%
“…Column chromatography and crystallization of fraction 1 (Fr. 1) yielded white needle-like crystals (19 mg) which were separated from the mother liquor and were named compound 1 and identified as β-sitosterol by comparing with previous literature reports . Fraction pool Fr.…”
Section: Resultsmentioning
confidence: 83%
“…It is worth noting that β -sitosterol has antibacterial potential. When studying against Salmonella typhi and Escherichia coli strains, the values of growth inhibition zones were 20 and 35 mm, respectively [ 28 ]. The activity of a β -sitosterol chloroform extract of M. parviflora roots against S. aureus and E. coli was studied [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that β-sitosterol has antibacterial potential. When studying against Salmonella typhi and Escherichia coli strains, the values of growth inhibition zones were 20 and 35 mm, respectively [28].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there are γ-sitosterol (25.76%), n-hexadecanoic acid (4.27%) and (Z)-11octadecenoic acid (3.16%) are reported to as potent broad spectrum antimicrobial [37][38][39][40][41]. Moreover, it has been demonstrated that the SP extracts have antimicrobial effect and inhibited both Gram-positive and Gram-negative bacteria because the presence of carvacrol ( 0.57%) which is confirmed by Memar, M.Y., et al, 2017 [42].…”
Section: Discussionmentioning
confidence: 99%